Discrepancy Analysis of Load–Displacement in the Combination Space for Concrete Box Girder Assessment - Ye, X.F.; Ogai, H.; Kim, C.W. (Проблемы прочности, 2018)
The combination space concept had its origin in the theory of subspace and combinatorics. The combination space may be treated as the space reconstruction through combination, as well as the subspace one. Several new analytical methods are proposed based on combination principles applied to some operations. Концепция пространства комбинаций возникла из теории подпространства и комбинаторики. Пространство комбинаций может рассматриваться перестраиванием как пространства, так и подпространства. Предложен ряд новых аналитических методов, основанных на принципах комбинации применительно к некоторым операциям.